Assessing the Performance of Female Mathematics Teachers in Light of Practicing Specific Professional Standards - Alkhazam , Awad Mufleh (Dirasat: Educational Sciences, 2023)
Objectives: This study aims to assess the performance of female mathematics teachers in relation to specific professional standards, as perceived by their students, taking into account grade and academic stream variables. Methods: The study employed a descriptive survey method and utilized a validated and reliable questionnaire consisting of 54 items across six domains. The study sample included 120 female students from the Directorate of Education, Qasabah of Mafraq District, Jordan. Results: The findings indicated no statistically significant differences (α = 0.05) in the overall average performance of female teachers across all domains of the study tool. Similarly, no significant differences were observed in dealing with students, student learning evaluation, ranking, and instructions organization. Furthermore, grade-level variations were not significant across most domains, except for classroom management and organization, which favored the second secondary grade, and in-school activities, which favored the first secondary grade. Notably, female mathematics teachers exhibited statistically significant differences in class management and organization, as well as in teaching methods. Additionally, academic stream significantly influenced in-school activities, with the literary stream demonstrating higher performance. Conclusions: Based on the results, it is recommended to provide training courses for female teachers that focus on promoting and implementing in-school activities.